Innovation and Continuous Improvement in Islamic Education: A Literature Review on Concepts, Implementation, and Challenges in the Digital Era - Prasasti, Weni Febriliani Eka; Julaiha, Siti (Journal of Educational Management Research, 2025)
This study aims to examine the concepts, implementation, and challenges of innovation and continuous improvement in Islamic education in the digital era through a literature review. The research method involves systematic searches of national and international journal databases, followed by thematic analysis to synthesize key findings. The results show that: (1) Islamic education innovation includes curriculum updates, interactive teaching methods, and the use of digital technology; (2) continuous improvement in schools/madrassas is often implemented through Total Quality Management (TQM) principles and the PDCA cycle; (3) digital technology expands access and enhances teaching methods but presents challenges in terms of human resources, infrastructure, and policy; (4) successful implementation depends on Leadership, teacher training, and stakeholder collaboration. The study concludes that integrating quality management strategies, technological capacity, and contextual approaches to the curriculum is crucial for sustainable innovation. The study provides recommendations for policymakers, educational managers, and researchers to develop implementation models responsive to local conditions.